Efektivitas Kepribadian Diri dalam Meningkatkan Antusiasme Peserta Didik - Hanifa Arifin, Millatina; Selvia, Sely; Samsul Arifin, Muhammad (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
The main component that determines the level of active learning of students is the enthusiasm of students. Learners' enthusiasm for learning can be assessed and measured by their interest in learning, attention to learning, motivation to learn, and knowledge that has an impact on optimal learning outcomes. This study aims to examine the effectiveness of self-personality in increasing learners' enthusiasm. The method used in this research is a literature study or by using a literature review of secondary sources, namely several journals that are by the research question. The model used is an interactive model that aims to assess research data qualitatively including data collection, data reduction, data presentation and conclusions. The result of this research study is to find out the percentage of self-personality in increasing students' enthusiasm.